(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The hydrochemical composition of the largest lakes in Yakutsk – Beloye, Khatyng-Yuryakh, Ytyk-Kyuel, Sergelyakh, Saisary, was analyzed based on a comprehensive study from 2009 to 2023. The studied lakes are predominantly sodium hydrocarbonate with medium mineralization and moderately hard water. The main contribution to the total volume of cations is made by Na+ and Ca2+, HCO3– and Cl– anions. A decrease in mineralization with a low approximation reliability is observed. Variation in water hardness values directly depends on the content of Ca2+ and Mg2+ cations and HCO3–. The average value of suspended solids is significantly higher than the existing Maximum Concentration Limit (MCL), the change in their content in each lake is individual, the highest was found in lakes Beloye, Saisary and Khatyng-Yuryakh. The most significant factor in the formation of the hydrochemical regime is mineralization and water hardness. The established patterns are characteristic in general for the entire sample, which reflects the specifics of the formation of the hydrochemical regime of urban lakes. The microelement composition is characterized by an increase in the concentrations of Pb, Ni and Fe. Ecological and geochemical analysis showed that the most polluted lakes are Beloye, Saisary and Khatyng-Yuryakh.